Augmentin as prophylaxis in elective colon surgery - Szczygieł, Bruno; Polański, Jerzy; Bielecki, Krzysztof; P. Nowacki, Marek; Popiela, Tadeusz; Tołłoczko, Tadeusz (Contemporary Oncology/Współczesna Onkologia, 1999)
A prospective, multi- centre, randomised trial was carried out in 11 hospitals in three countries (Poland, Czech Republic and Hungary) in order to compare the efficiency of amoxycillin- clavulanic acid (Augmentin) versus cefuroxime plus metronidazole as antibiotic prophylaxis in patients undergoing elective colorectal surgery. Eligible patients were randomly assigned to receive either 3 intravenous doses of augmentin 1,2 g or 3 intravenous doses of cefuroxime (1,5) plus metronidazole (500mg) on the induction of anaesthesia and 8 and 16 hours later. Among 353 randomised patients, 174 received 3 doses of augmentin and 179 three doses of cefuroxime plus metronidazole. Wound infections occurred in 11,5% of patients who received augmentin and in 12,3% of patients who received cefuroxime plus metronidazole. There were no statistically significant differences between prophylactic regimens with regard to the incidence of wound infection or the types of organisms isolated from these wounds. The results of the trial demonstrate that both prophylactic regimens were well tolerated and have similar efficiency when used for prophylaxis of infection after elective colorectal surgery. The use of augmentin as antibiotic prophylaxis is recommended because of its easier use and lower cost.